Primary Cervical Carcinoma Cell Lines Overexpress Epithelial Cell Adhesion Molecule (EpCAM) and Are Highly Sensitive to Immunotherapy With MT201, a Fully Human Monoclonal Anti-EpCAM Antibody - Richter, Christine E. (2010)
INTRODUCTION: Epithelial cell adhesion molecule (EpCAM) is a surface glycoprotein highly differentially expressed in many epithelial malignancies. The goal of this study was to evaluate the expression of EpCAM and the potential of MT201 (adecatumumab), a human monoclonal antibody targeting EpCAM, against multiple primary cervical carcinoma cell lines. METHODS: Epithelial cell adhesion molecule expression was evaluated by real-time polymerase chain reaction and flow cytometry in a total of 8 primary cervical cancer cell lines. Sensitivity to MT201-mediated cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity was tested in standard 4-hour (51)Cr release assays. To investigate the effect of interleukin-2 (IL-2) on MT201-mediated ADCC, 4-hour (51)Cr release assays were also conducted in the presence of low doses of IL-2. RESULTS: High messenger RNA expression by real-time polymerase chain reaction and high EpCAM surface expression by flow cytometry were detected in 4 (50%) of 8 primary cervical carcinoma cell lines. With no exception, the primary cell lines derived from clinically aggressive tumors showed EpCAM overexpression. Whereas these cell lines were highly resistant to complement-dependent cytotoxicity and natural killer (NK)-dependent cytotoxicity in vitro (range of killing, 4%–19%), EpCAM-positive cell lines showed high sensitivity to MT201-mediated ADCC (range of killing, 23%–59%). Incubation with IL-2 in addition to MT201 significantly increased the cytotoxic activity against EpCAM-positive cervical cancer cell lines (P = 0.007). Addition of human serum also further increased the MT201-mediated killing of EpCAM-positive cell lines (P = 0.03). CONCLUSIONS: Epithelial cell adhesion molecule is highly expressed in primary cervical carcinoma cell lines, and these biologically aggressive tumors are highly sensitive to MT201-mediated cytotoxicity in vitro. MT201 may represent a novel, potentially highly effective treatment option for patients with cervical carcinoma, especially for those with advanced, recurrent, or metastatic disease refractory to standard salvage therapy.